School bullying : new perspectives on a growing problem - Dupper, David R. (New York : Oxford University Press, 2013)
'School Bullying' is unique in utilising a larger cultural context and international perspective that broadens the traditional conceptualisation of bullying and that promotes creative approaches to a seemingly intractable and complex problem. In addition, the book investigates several 'under the radar' forms of bullying (e.g., religious bullying, bullying by teachers and other adults in schools), as well as the unique challenges in assessing these largely unacknowledged forms of bullying in today's U.S. public schools.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Bullying in schools -- United States; Bullying in schools -- United States -- Prevention